2022
DOI: 10.3389/fphar.2022.977440
|View full text |Cite
|
Sign up to set email alerts
|

Apamin structure and pharmacology revisited

Abstract: Apamin is often cited as one of the few substances selectively acting on smallconductance Ca 2+ -activated potassium channels (K Ca 2). However, published pharmacological and structural data remain controversial. Here, we investigated the molecular pharmacology of apamin by two-electrode voltage-clamp in Xenopus laevis oocytes and patch-clamp in HEK293, COS7, and CHO cells expressing the studied ion channels, as well as in isolated rat brain neurons. The microtitre broth dilution method was used for antimicrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 79 publications
1
13
0
1
Order By: Relevance
“…Finally, additional testing showed that the reinforcement of the positive charges on both nitrogens, obtained by Nmethylation yielding quaternary analogues, resulted in an increased affinity for SK targets (data not shown). This is in accordance with the pharmacophore 15,16 and with previous investigations of related molecules, such as tetrandrine and its stronger N-methylated analogue, and the AG525 isomers, which were also N-methylated, yielding stronger derivatives. 22 Such quaternary compounds are, however, less interesting in therapeutic contexts, as their biological availability is strongly reduced due to cell-membrane impermeability, especially when considering the central nervous system distribution.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Finally, additional testing showed that the reinforcement of the positive charges on both nitrogens, obtained by Nmethylation yielding quaternary analogues, resulted in an increased affinity for SK targets (data not shown). This is in accordance with the pharmacophore 15,16 and with previous investigations of related molecules, such as tetrandrine and its stronger N-methylated analogue, and the AG525 isomers, which were also N-methylated, yielding stronger derivatives. 22 Such quaternary compounds are, however, less interesting in therapeutic contexts, as their biological availability is strongly reduced due to cell-membrane impermeability, especially when considering the central nervous system distribution.…”
supporting
confidence: 92%
“…Apamin is a specific ligand of the SK family and has an extremely high affinity for all three subtypes, in the nanomolar to sub-nanomolar range, with no effective subtype selectivity. More precisely, its blocking activity, in order, is stronger on SK2 with an IC 50 of 87.7 pM, than on SK3 with an IC 50 of 2.3 nM, and finally on SK1 channels with an IC 50 of 4.1 nM. …”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Particularly, SK2 channels are the most sensitive to apamin with a half maximal blocking concentration (IC50: 27-140 pM, SK1 are less sensitive (IC50: 0.7-12 nM), and SK3 show an intermediate sensitivity to apamin (IC50: 0.6-4 nM). Importantly, apamin has no inhibitory effects on other types of K + channels as well as on ion channels from other families as it was confirmed recently on a broad repertoire of channel proteins [6]. For functional identification of IK activity, TRAM-34, the analog of clotrimazole, a potent and selective blocker of IK (KCa3.1), is widely used [7,8].…”
Section: Introductionmentioning
confidence: 94%
“…Differentiation into “apamin‐sensitive” and “apamin‐insensitive” K Ca has been common since 1980s to indicate the small‐conductance K Ca channels (K Ca 2 or SK Ca ) and intermediate‐conductance (K Ca 3.1 or IK Ca ) or large‐conductance K Ca channels (K Ca 1.1 or BK Ca ; Burgess et al, 1981; Pennefather et al, 1985; Romey & Lazdunski, 1984). The cloning and expression of mammalian K Ca 2 channels in Xenopus laevis oocytes was then used to demonstrate apamin activity on the molecular level (Grunnet et al, 2001; Köhler et al, 1996), whereas large‐scale pharmacological profiling revealed a unique selectivity of apamin (Kuzmenkov et al, 2022). Human β‐defensin 2, plectasin from the fungus Pseudoplectania nigrella , and peptide AcK1 from the parasitic worm Ancylostoma ceylanicum serve as examples of non‐venom‐derived ligands of K + channels (Chhabra et al, 2014; Xiang et al, 2015; Yang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%